Sediment Yield Modeling as Sediment Management Strategies Towards Sustainability of Hydropower Reservoirs in Malaysia - Razad A.Z.A.; Samsudin S.H.; Abbas N.A.; Setu A.; Mohd Sidek L.; Jung K.; Sharip Z. (Springer, 2023)
Reservoir sedimentation is common in lakes and reservoirs. Heavy sedimentation is observed in reservoirs in Cameron Highlands and the trends are uprising in other lakes or reservoirs in Malaysia. Mitigation measures that can be undertaken by the reservoir managers are limited within the reservoir. Pollutant control at sources is difficult to be implemented. To develop effective sediment management strategies for hydropower reservoirs, sediment inflow rate must be determined. This paper compiles sedimentation rate for hydropower reservoirs in Malaysia based on soil loss model calculated in GIS, bathymetry survey and sediment sampling works in Ringlet (Cameron Highlands), Chenderoh (Perak) and Kenyir (Terengganu). The analysis show that Ringlet has the highest sedimentation rate, while the rate for Kenyir and Chenderoh are still of low risk. 2020, Springer Nature Singapore Pte Ltd.